2017
DOI: 10.4111/icu.2017.58.2.82
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of phosphodiesterase type 5 inhibitors for the treatment of distal ureteral calculi: A systematic review and meta-analysis

Abstract: PurposeTo determine the efficacy of phosphodiesterase type 5 inhibitors (PDE5i) as medical expulsive therapy (MET) for the treatment of distal ureteral calculi.Materials and MethodsA search strategy was conducted in the MEDLINE, CENTRAL, and Embase databases. Searches were also conducted in other databases and unpublished literature. Clinical trials were included without language restrictions. The risk of bias was evaluated with the Cochrane Collaboration's tool. An analysis of random effects due to statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…With regard to other indications related to nephropathy and cardiomyopathy, sildenafil has also been tested against media-induced nephropathy, and tadalafil is being explored in the context of kidney stones and endocrine cardiomyopathy (Table 3). A meta-analysis of older clinical studies suggest PDE5i's could be an effective medical expulsive therapy for distal ureteral calculi, albeit not significantly improved relative to tamsulosin (164). With regard to the brain, two early-stage clinical trials are testing the ability of sildenafil to reverse concussion-related reductions in cerebrovascular reactivity (Table 3).…”
Section: Pde5 Inhibitorsmentioning
confidence: 99%
“…With regard to other indications related to nephropathy and cardiomyopathy, sildenafil has also been tested against media-induced nephropathy, and tadalafil is being explored in the context of kidney stones and endocrine cardiomyopathy (Table 3). A meta-analysis of older clinical studies suggest PDE5i's could be an effective medical expulsive therapy for distal ureteral calculi, albeit not significantly improved relative to tamsulosin (164). With regard to the brain, two early-stage clinical trials are testing the ability of sildenafil to reverse concussion-related reductions in cerebrovascular reactivity (Table 3).…”
Section: Pde5 Inhibitorsmentioning
confidence: 99%
“…Tadalafil, a more accessible drug, but a PDEI, has also been proposed as a viable alternative for MET. Studies and meta-analysis that compared tadalafil and tamsulosin for the treatment of distal ureteral stones from 5 to 10 mm have shown conflicting results ( 9 , 10 ). The last meta-analysis about this subject was published in 2017 with 565 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The most common PDE5 inhibitor that has been studied as a medical expulsive treatment option is tadalafil 10 mg. Early studies have shown promising results [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%